Integrasi Sains dan Agama serta Implikasinya terhadap Pendidikan Islam - Iis Arifudin (Edukasia Islamika : Jurnal Pendidikan Islam, 2016)
Integration of science and religion means combining science and religion. However, it does not completely mix them because they have their own characteristics. The integration of science and religion is a very possible thing in Islamic paradigm because it is based on the concept of tauhid. It is necessary for science and religion to emerge the awareness of holistic and comprehensive concept in education. By integrating science and religion especially in Islamic education system, the students will be motivated to conduct a scientific research by linking it to religion. Moreover, it will also encourage the teachers to be more creative in teaching the students and educate the school participants to respect other religions as well.